B2, an abscisic acid mimic, improves salinity tolerance in winter wheat seedlings via improving activity of antioxidant enzymes - Yu, Chunxin; Zhou, Fan; Wang, Ruonan; Ran, Zhaojin; Tan, Weiming; Jiang, Linjiang; Cui, Shunyan; Xie, Zhouli; Xiao, Yitao; Zhou, Yuyi; Duan, Liusheng (Frontiers in Plant Science, 2022)
Salinity severely inhibits growth and reduces yield of salt-sensitive plant like wheat, and this effect can be alleviated by plant growth regulators and phytohormones, among which abscisic acid (ABA) plays a central role in response to various stressful environments. Owing to ABA high photosensitive to light disruption, thus this limits its application. Here, based on pyrabactin (a synthetic ABA agonist), we designed and synthesized a functional analog of ABA and named B2, then evaluated its role in salt resistance using winter wheat seedling. The phenotypes showed that B2 significantly improved the salt tolerance of winter wheat seedlings by elevating the biomass. The physiological analysis found that B2 treatment reduced the generation rate of O2·-, electrolyte leakage, the content of proline and the accumulation of MDA and H2O2, and also significantly increased the contents of endogenous hormones ZR and GA. Further biochemical analysis revealed that the activities of various antioxidant enzymes including superoxide dismutase (SOD), peroxidase (POD) and ascorbate peroxidase (APX) were enhanced by B2, the activities of antioxidase isozymes SOD3, POD1/2 and APX1/2 were particularly increased, largely resembling ABA treatment. The abiotic stress response-related gene TaSOS1 was significantly upregulated by B2, while the TaTIP2;2 gene was suppressed. In conclusion, an ABA analog B2 was capable to enhance salt stress tolerance in winter wheat seedlings by stimulating antioxidant system, providing a novel regulator for crops better survival in saline soils and improving crop yield.